HUBUNGAN PENGEMBANGAN PEGAWAI DENGAN EFEKTIVITAS KERJA PEGAWAI DI KANTOR KECAMATAN BARUMUN KABUPATEN TAPANULI SELATAN - Mhd. Faisal Amrin Siregar (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
Sub-district represents the front-line government agent in delivering public services to citizens. Considering this strategic function, personnel work effectiveness is definitely required. Evidence shows that personnel work effectiveness has yet to improve. Based upon existing phenomena, personnel development through trainings and job promotion significantly correlates with personnel work performance.